Histopathology, salivary flow and ultrasonography of the parotid gland: three complementary measurements in primary Sjögren's syndrome. (21st October 2021) - Mossel, Esther; van Ginkel, Martha S; Haacke, Erlin A; Arends, Suzanne; Liefers, Silvia C; Delli, Konstantina; van Nimwegen, Jolien F; Stel, Alja J; Spijkervet, Fred K L; Vissink, Arjan; van der Vegt, Bert; Kroese, Frans G M; et al.
Abstract: Objective: The involvement of salivary glands in primary SS (pSS) can be assessed in different ways: histopathology, salivary flow and ultrasonography. To understand the relative value of these different approaches, it is crucial to understand the relationship between them. As we routinely perform these three modalities in the parotid gland for disease evaluation, our aim was to investigate the construct validity between these modalities in one and the same gland. Methods: Consecutive sicca patients underwent a multidisciplinary diagnostic workup including parotid gland biopsy, collection of parotid gland–specific saliva and parotid gland ultrasonography. Patients who were classified as pSS according to the ACR-EULAR criteria were included. Construct validity was assessed using Spearman's correlation coefficients. Results: The 41 included pSS patients completed a full workup within a mean time interval of 2.6 months. Correlations between histopathological features and stimulated parotid salivary flow were fair ( ρ  = −0.123 for focus score and ρ  = −0.259 for percentage of CD45 + infiltrate). Likewise, poor correlations were observed between stimulated parotid salivary flow and parotid ultrasonography ( ρ  = −0.196). Moderate to good associations were found between the histopathological items focus score and the percentage of CD45 + infiltrate, with parotid US scores (total US score: ρ  = 0.510 and ρ  = 0.560; highest for homogeneity: ρ  = 0.574 and ρ  = 0.633). Conclusion: Although pSS-associated ultrasonographic findings did correlate with histopathological features, the three modalities that evaluate salivary gland involvement assess different (or at best partly related) constructs. Therefore histopathology, salivary flow and ultrasonography are complementary measurements and cannot directly replace each other in the workup of pSS.